Molybdenum carbide-based electrocatalysts for CO tolerance in proton exchange membrane fuel cell anodes - Hassan, Ayaz (2014)
The activity, stability and CO tolerance of molybdenum carbide-based electrocatalyts were studied in anodes of proton exchange membrane fuel cells (PEMFCs). To this purpose, carbon-supported molybdenum carbide (Mo 2C/C) was prepared by an ultrasonic method, and was used as catalyst support in the anode of a PEMFC. Pt and PtMo nanoparticles were deposited on this Mo2C/C by the formic acid reduction method. The physical properties of the resulting electrocatalysts were studied by X-ray diffraction (XRD), transmission electron microscopy (TEM), energy dispersive spectroscopy (EDS), X-ray absorption near edge structure (XANES), scanning electron microscopy (SEM) and wavelength dispersive spectroscopy (WDS). Electrochemical characterizations were carried out by single cell polarization measurements, CO stripping, cyclic voltammetry (CV) and online mass spectrometry (OLMS). CV and OLMS experiments were performed to evaluate the stability and CO tolerance of the electrocatalysts. The results obtained for the carbide-based electrocatalysts were compared with those obtained for carbon-supported PtMo and Pt electrocatalysts. It was observed that Pt and PtMo supported on Mo 2C/C present a better stability than PtMo supported on carbon. CV and WDS results evidenced a partial dissolution of Mo from the anode and its migration toward cathode during the cell operation. On the basis of polarization measurements and cyclic voltammograms, it was concluded that the stability of anode electrocatalysts can be improved by the use of molybdenum carbide as catalyst support.